Modeling of micro-grid with the consideration of total harmonic distortion analysis - Ibrahim Alhamrouni; Wira Wahab; M. Salem; Nadia H. A. Rahman; Lili Awalin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
With the rapid expansion of electricity grid, there yet still places to be covered considering their remote location. Micro-grid (MG) is a solution in this scenario, in fact, there is actually many cases where MG is used in case of emergency and act as a backup to the main electrical grid. By disconnecting itself from the larger grid, a grid that can have many problems, the micro-grid becomes much more flexible in its operations and by continuing to power households and communities alike. Besides grid-connected mode, it is necessary for the MG to operate in autonomous mode. By operating in islanded mode, micro-grids must be able to supply critical load without interruption, run at specific values for voltage and power and extract the maximum power from the distributed generations (DG). Therefore, the modeling of microgrid network considering solar photovoltaic(PV) and wind turbine generation (WTG) system as the distributed generation have been modeled using Matlab/Simulink in this research. Apart from that, the observation of total harmonic distortion(THD) between two operation modes of grid-connected and the islanded-mode is presented in order to analyze the power quality stability towards two operations MG network with same loads size and network parameters.